Unbounded : On the Interior and Interiority. - Huppatz, D. J. (Cambridge Scholars Publishing, 2015)
In interior design, the definition and popular perception of the interior has long been concerned with bounded spaces, and with the relationship between private and public realms. However, two issues have challenged traditional boundaries between interior and exterior, and private and public: first, the emergence of new technological practices, and second, a broader understanding of diverse cultures. Popular perceptions of public and private space are currently being revised, and the interior ...